2014
DOI: 10.1016/j.jviromet.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Construction of replication competent plasmids of hepatitis B virus subgenotypes A1, A2 and D3 with authentic endogenous promoters

Abstract: Hepatitis B virus (HBV) is hyperendemic to southern Africa, with genotype A of HBV being the predominant genotype, and subgenotype A1 prevailing. Infection with this subgenotype is associated with rapid disease progression, and high frequency of hepatocellular carcinoma development. The objectives of our study was to construct recombinant 1.28 mer replication competent HBV DNA plasmids of subgenotypes A1, A2 and D3 containing authentic endogenous HBV promoters and to follow their replication in vitro after tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
2
14
1
Order By: Relevance
“…These researchers observed that HBV DNA replication was higher for the Asian genotypes than for European genotypes and that the levels of secreted HBeAg generally correlated with intracellular core-associated DNA levels, whereas the levels of HBsAg varied across genotypes, being highest for genotype A and lowest for genotype D. Although these researchers observed no difference in HBV DNA levels between European genotypes A and D, both of these genotypes replicated poorly in this study (10) making it difficult to draw meaningful conclusions regarding their comparative replication phenotype. A more recent study utilizing 1.28-fold copies of the HBV genome concluded that the HBV genotype D replicated at lower levels than the HBV genotype A, although HBV replication was again low in this study (11). Direct comparisons of the replication phenotype of genotypes B and C utilizing 1.24-mer clones (10) or tandem dimers (12) identified differences in the comparative replication phenotypes of genotypes B and C in these studies, with Sugiyama et al (10) identifying higher levels of DNA replication for genotype C than for genotype B, in contrast to the findings of Qin et al (12), who identified higher levels of DNA replication for genotype B. Genotype differences in virus secretion were also observed, with Qin et al observing higher levels of secretion for genotype C than for genotype B (12), in contrast to Sugiyama et al, who observed similar levels of virion secretion for genotypes B2 (Ba) and C (10).…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…These researchers observed that HBV DNA replication was higher for the Asian genotypes than for European genotypes and that the levels of secreted HBeAg generally correlated with intracellular core-associated DNA levels, whereas the levels of HBsAg varied across genotypes, being highest for genotype A and lowest for genotype D. Although these researchers observed no difference in HBV DNA levels between European genotypes A and D, both of these genotypes replicated poorly in this study (10) making it difficult to draw meaningful conclusions regarding their comparative replication phenotype. A more recent study utilizing 1.28-fold copies of the HBV genome concluded that the HBV genotype D replicated at lower levels than the HBV genotype A, although HBV replication was again low in this study (11). Direct comparisons of the replication phenotype of genotypes B and C utilizing 1.24-mer clones (10) or tandem dimers (12) identified differences in the comparative replication phenotypes of genotypes B and C in these studies, with Sugiyama et al (10) identifying higher levels of DNA replication for genotype C than for genotype B, in contrast to the findings of Qin et al (12), who identified higher levels of DNA replication for genotype B. Genotype differences in virus secretion were also observed, with Qin et al observing higher levels of secretion for genotype C than for genotype B (12), in contrast to Sugiyama et al, who observed similar levels of virion secretion for genotypes B2 (Ba) and C (10).…”
contrasting
confidence: 57%
“…Intracellular antigens in cell lysates were detected by immunoblotting as previously described (16) using antibodies against the HBsAg (H166 antibody kindly donated by Paul Coleman, Abbott Laboratories, Abbott Park, IL). For the detection of HBcAg, proteins were first immunoprecipitated (16) from 1.5 ml of cell lysate using an in-house monoclonal antibody (1D8) (11,24). For the detection of extracellular proteins, virions were immunoprecipitated from 15 ml of supernatant, as previously described (16).…”
Section: Methodsmentioning
confidence: 99%
“…1.28-mer replication-competent plasmids for wild-type subgenotypes A1 (KM519453), A2 (KM519454), and D3 (KM519455) were constructed and were able to replicate and express proteins in vitro [31]. Ethics approval to perform this study was obtained from the University of the Witwatersrand Research Ethics Committee (Medical), Johannesburg, South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…Huh7 cells were transfected as described previously [31]. Twenty-four hours prior to transfection, 6 × 10 5 Huh7 cells were plated into each of the 6-cm culture dishes containing either 6 coverslips for indirect immunofluorescence or no coverslips for immunoblotting or reverse transcriptase (RT) polymerase chain reaction (PCR) (or 6 × 10 3 cells plated into 96-well tissue culture plates for ELISA) and incubated overnight at 37°C in a humidified incubator containing 5% (w/v) CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation